2002
DOI: 10.1002/cncr.10252
|View full text |Cite
|
Sign up to set email alerts
|

National Cancer Data Base report on malignant paragangliomas of the head and neck

Abstract: BACKGROUNDMalignant paragangliomas of the head and neck are rare, with previous reports limited to nine or fewer patients. The current review included 59 cases extracted from the National Cancer Data Base that were diagnosed between 1985–1996.METHODS The primary criterion for inclusion in the current study was verified metastatic spread from a paraganglioma of the head and neck. Patterns of presentation and treatment as well as clinically relevant associations were demonstrated in contingency tables. Relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
351
4
34

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(409 citation statements)
references
References 26 publications
8
351
4
34
Order By: Relevance
“…Currently, malignancy cannot be predicted with certainty, although some histological or gene expression features might be suggestive of malignancy (Strong et al 2008). The prognosis of malignant PCC and PGL is poor, with a 5-year mortality rate O50% (Lee et al 2002, Chrisoulidou et al 2007. There is currently no effective or curative treatment, but surgery, chemotherapy, and radiotherapy are beneficial in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, malignancy cannot be predicted with certainty, although some histological or gene expression features might be suggestive of malignancy (Strong et al 2008). The prognosis of malignant PCC and PGL is poor, with a 5-year mortality rate O50% (Lee et al 2002, Chrisoulidou et al 2007. There is currently no effective or curative treatment, but surgery, chemotherapy, and radiotherapy are beneficial in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a well-established familial association that has been observed in upward of 10% of PGLs, owing predominantly to mutations in three of the four succinate dehydrogenase subunit genes (SDHB, SDHC, and SDHD). 1,5 This genetic predisposition carries an increased risk for multifocal tumor development, with an 80% chance of multicentricity in familial cases as opposed to only a 10 to 20% chance in sporadic cases. 1,5 The genetic characteristics of familial PGLs have been well described in various publications, such as Martin et al 2007 and Papaspyrou et al 2011, although SDHD is the most commonly implicated gene in the development of benign familial PGLs of the head and neck, and SDHB mutations have the highest rate of developing malignant PGLs.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 This genetic predisposition carries an increased risk for multifocal tumor development, with an 80% chance of multicentricity in familial cases as opposed to only a 10 to 20% chance in sporadic cases. 1,5 The genetic characteristics of familial PGLs have been well described in various publications, such as Martin et al 2007 and Papaspyrou et al 2011, although SDHD is the most commonly implicated gene in the development of benign familial PGLs of the head and neck, and SDHB mutations have the highest rate of developing malignant PGLs. 5, 12 Papaspyrou et al did report one case of their 175 patient series in which the patient was found to be positive for a mutation in the SDHC gene after presenting with multiple malignant PGLs of the ITF, carotid body, and jugulotympanic region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations